A bi-stable device for simultaneous vibration absorption and energy harvesting using bi-stable piezoelectric composite laminate. (15th June 2023) - Li, Ming; Yu, Dong; Li, Yanqi; Liu, Xiaohui; Dai, Fuhong
Abstract: A bi-stable device is presented for simultaneous vibration absorption and energy harvesting by introducing the piezoelectric element into the bi-stable nonlinear energy sink (BNES), which is called the bi-stable piezoelectric absorber (BPZA). BPZA only consists of the cantilever bi-stable piezoelectric composite laminate (BPCL) and tip masses. This BPZA is a lightweight, simple and reliable structure since it does not need any external devices to maintain bistability. A finite element model (FEM) and an equivalent theoretical model are developed to model a harmonically excited linear oscillator coupled with BPZA. The Runge-Kutta method is used to solve the theoretical model numerically. The effects of the excitation amplitude, the tip mass of BPZA and the load resistance are considered on the vibration suppression efficiency and energy harvesting of BPZA. The results show adjusting these parameters can improve the vibration suppression efficiency and energy harvesting of BPZA. In addition, the experimental prototype is prepared and verifies the rightness of the finite element model and theoretical model. The BPZA achieves the goal of higher power density at lower acceleration and simultaneously has a good vibration absorption effect. Maximum power of 15.8mW is generated at an excitation frequency of 22 Hz and acceleration of 0.5 g.